Perancangan Desain Bilik Ganti Baju Bagi Komunitas Kabaret - Nadia Zulfa; Maharani Dian Permanasari (Jurnal Desain Produk Nasional, 2024)
The design of a fitting chamber for the cabaret community using the design thinking method is a creative approach aimed to generate an innovative solution that fulfills the needs of the cabaret community in Bandung. This method is used to understand the challenges faced by the cabaret community in terms of fitting area, along with creating an appropriate design which caters to the hopes of the user. The design process uses the design thinking method which involved for main phases: empathize, research, ideation, and prototyping. In the empathize phase, information regarding the needs and preferences of the members of the cabaret community, along with the problems that might occur in the dressing room at present is gathered. The next phase involved further exploration in regard to shape configuration, appropriate material selection, and user experience. The design team conducted observation, interview, and analysis to understand the needs and hopes of the user in regards to a fitting space appropriate for the limited space available during cabaret shows. The prototyping phase involved model fabrication or preliminary design of the proposed fitting chamber. This prototype is used to test and acquire feedback from the members of cabaret community. Implementation of design thinking method within the design of a fitting chamber for the cabaret community is expected to generate a functional, comfortable, and appropriate solution for the members of the community. This solution will elevate user experience in using a fitting area, pushing for active participation, and supporting the development of the cabaret community as a whole.